2023
DOI: 10.3390/nu15061433
|View full text |Cite
|
Sign up to set email alerts
|

Industrial and Ruminant Trans-Fatty Acids-Enriched Diets Differentially Modulate the Microbiome and Fecal Metabolites in C57BL/6 Mice

Abstract: Industrially originated trans-fatty acids (I-tFAs), such as elaidic acid (EA), and ruminant trans-fatty acids (R-tFAs), such as trans-palmitoleic acid (TPA), may have opposite effects on metabolic health. The objective was to compare the effects of consuming 2–3% I-tFA or R-tFA on the gut microbiome and fecal metabolite profile in mice after 7 and 28 days. Forty C57BL/6 mice were assigned to one of the four prepared formulations: lecithin nanovesicles, lecithin nanovesicles with EA or TPA, or water. Fecal samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Accordingly, Adlercreutzia and Anaeroplasma (class Mollicutes; order Anaeroplasmatales; phylum Tenericutes) were specific to the NC group; Bacteroides and Shigella were enriched in the EA group; while AF 12 together with [Prevotella] in the family of [Paraprevotellaceae] dominated the LEA group. Based on the study conducted by Mohammadi et al (2023) , it could be concluded that changes in gut microbiota structure were highly correlated with the position of double bonds in TFAs.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, Adlercreutzia and Anaeroplasma (class Mollicutes; order Anaeroplasmatales; phylum Tenericutes) were specific to the NC group; Bacteroides and Shigella were enriched in the EA group; while AF 12 together with [Prevotella] in the family of [Paraprevotellaceae] dominated the LEA group. Based on the study conducted by Mohammadi et al (2023) , it could be concluded that changes in gut microbiota structure were highly correlated with the position of double bonds in TFAs.…”
Section: Resultsmentioning
confidence: 99%